Управління мотиваційними процесами в органах публічної влади - Коваль, Аліна Володимирівна; Koval, Alina Volodymyrivna (Ірпінь, 2024)
Робота полягає в розкритті теоретичних та практичних аспектів управління мотиваційними процесами, розробленні та обґрунтуванні рекомендацій щодо розвитку мотивації в органах публічної влади

The work consists in revealing the theoretical and practical aspects of management of motivational processes, development and justification recommendations on the development of motivation in public authorities
Management of motivational processes in public authorities
Keywords: мотивація; мотиваційні процеси; орган публічної влади; посадова особа; службовці; методи; винагорода; механізми; теорії; motivation; motivational processes; public authorities; official; employees; methods; reward; mechanisms; theories